2014
DOI: 10.1152/physrev.00040.2013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Shaping of Cellular Membranes by Phospholipids and Membrane-Deforming Proteins

Abstract: All cellular compartments are separated from the external environment by a membrane, which consists of a lipid bilayer. Subcellular structures, including clathrin-coated pits, caveolae, filopodia, lamellipodia, podosomes, and other intracellular membrane systems, are molded into their specific submicron-scale shapes through various mechanisms. Cells construct their micro-structures on plasma membrane and execute vital functions for life, such as cell migration, cell division, endocytosis, exocytosis, and cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
216
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 206 publications
(218 citation statements)
references
References 335 publications
(388 reference statements)
1
216
0
1
Order By: Relevance
“…Our group and others have shown that PACSIN2 localizes to and functions at caveolae (Hansen et al, 2011;Koch et al, 2012;Senju et al, 2011). Moreover, BAR domain proteins are known to bind to negatively-charged lipids, including phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ] (Suetsugu et al, 2014), and PtdIns(4,5) P 2 is enriched at caveolae (Fujita et al, 2009). S313 phosphorylation caused a decrease in the membrane-binding and tubulation abilities of PACSIN2.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our group and others have shown that PACSIN2 localizes to and functions at caveolae (Hansen et al, 2011;Koch et al, 2012;Senju et al, 2011). Moreover, BAR domain proteins are known to bind to negatively-charged lipids, including phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ] (Suetsugu et al, 2014), and PtdIns(4,5) P 2 is enriched at caveolae (Fujita et al, 2009). S313 phosphorylation caused a decrease in the membrane-binding and tubulation abilities of PACSIN2.…”
Section: Discussionmentioning
confidence: 86%
“…Proteins containing a membrane-sculpting Bin-Amphiphysin-Rvs (BAR) domain are evolutionarily conserved, and members of this family are found at various intracellular membrane structures, including clathrin-coated pits, compartments of the endocytic pathways, and membrane protrusions, such as filopodia and lamellipodia (Safari and Suetsugu, 2012;Suetsugu et al, 2014). BAR domain proteins form crescent-shaped homodimers and sense or generate membrane curvature through positively charged surfaces (Frost et al, 2008(Frost et al, , 2009Itoh and De Camilli, 2006;Peter et al, 2004;Suetsugu et al, 2010), thereby performing crucial roles in membrane remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of loss-of-function studies has addressed whether these observations have any cell biological or physiological importance. These analyses indeed frequently reveal phenotypes in endocytosis and/or neuronal morphology establishment -processes that involve extensive and spatially restricted changes in membrane topology Suetsugu et al, 2014) -thereby suggesting that BAR domain proteins are indeed crucial for shaping membranes in vivo (Fig. 3A).…”
Section: Working To Shape Membranesmentioning
confidence: 96%
“…Most BAR domain proteins have the ability to shape liposomes and many have also been reported to overcome the membrane tensions of living cells and to form tubules or membrane protrusions upon their overexpression Qualmann et al, 2011;Mim and Unger, 2012;Suetsugu et al, 2014). Recently, an increasing number of loss-of-function studies has addressed whether these observations have any cell biological or physiological importance.…”
Section: Working To Shape Membranesmentioning
confidence: 99%
“…3A, B, C . Lamellipodia are defined as the thinner regions located at the cell periphery where the actin fiber is much denser than in the remainder of the cell 9,[22][23][24] . However, in the lamellipodia definition, cellular polarity is not necessarily taken into account.…”
Section: Discussionmentioning
confidence: 99%